O amor concede eternidades: representação de Eros em contos de Mia Couto - Pereira, Francisca Kellyane Cunha (2025)
This research aims to present two representations of the feeling of love in the short stories of Mozambican writer Mia Couto. Based on the analysis of theories, symbols, and archetypes associated with love, femininity, masculinity, androgyny, and prohibition, the stories reveal two figurations of love: symbiosis, where there is a spiritual or physical union of subjects in the romantic bond, aligning with the concept of lovers’ androgyny; and prohibition, where the union of lovers is socially forbidden, leading them to transgression. The corpus of this study consists of four collections of Mia Couto’s short stories: Na Berma de Nenhuma Estrada (1987), Estórias Abensonhadas (1994), Contos do Nascer da Terra (2009), and Cada Homem é uma Raça (2013). Specific stories are analyzed to explore these themes: “Ezequiela, a humanidade”, “Ofélia e a eternidade”, “Isaura, para sempre dentro de mim”, “Joãotónio, no enquanto”, and “A princesa russa” depict characters experiencing amorous symbiosis; “O amante do comandante”, “A filha da solidão”, “Rosa Caramela”, “As lágrimas de Diamantinha”, “A viagem da cozinheira lacrimosa”, and “Prostituição auditiva” portray characters whose love relationships are forbidden by societal norms. The theoretical framework draws on the ideas of Plato (2012) in dialogue with the works of José Ortega y Gasset (2019), Octavio Paz (1993), Carl Jung (2005), Erich Fromm (1956), and Georges Bataille (1957) on love and eroticism. Additionally, it incorporates insights on Mia Couto’s writing from Fernanda Cavacas (2015), Maria Nazareth Fonseca (2008), Rita Chaves (2013), and Ana Mafalda Leite (2013).